BIOGENIC ZnO NPs BASED INTRACANAL MEDICAMENT AGAINST Enterococcus faecalis - MATTIGATTI, SUDHA; DATKHILE, KAILAS (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Aim: This study aimed to investigate the antibacterial efficacy of biogenic ZnO nanoparticles based intracanal medicament. Methodology: The biogenic ZnONP based irrigant solution was tested in vitro on Enterococcus faecalis (ATCC: 29212) with Sodium hypochlorite as positive control. The synthesis of ZnO NPs was carried out by green synthesis method using 0.1 M Zinc sulphate aqueous extract of Nophapodytes foetida plant. The biosynthesis of nanoparticles was confirmed by UV-Vis spectroscopy and characterized by XRD, and Scanning Electron Microscopy. The qualitative and quantitative antimicrobial activity of ZnO NPs was tested against gram positive Enterococcus faecalis bacteria. Results: The optical, structural and morphological analysis reveals the formation of ZnO nanostructures having flakes like morphology with size ranges from 20 to 35 nm. The inhibition zones was observed in all concentrations with positive control. The number of colony forming units dropped to zero at 500µg/mL suspension of ZnO NPs. Conclusion: Biogenic ZnO NPs can be used as an effective endodontic irrigant after checking its feasibility.